Three hops reliability model for Underwater Wireless Sensor Network - Ali, T. (Institute of Electrical and Electronics Engineers Inc., 2014)
Due to the instability of underwater environment, the reliable data transfers is more sensitive issue in Underwater Wireless Sensor Networks (UWSNs) as compare to land based sensor network. Underwater networks are mostly designed by acoustic sensor nodes and surface sinks that are connected to any onshore control center. Acoustic channel characteristics are create many problems like, low bandwidth; long propagation delays and high error channel rates that can cause to hamper the efficiency of UWSNs. With these constraints, it is very difficult task to design a routing protocol which has the ability to maximize the reliability of these networks. In this paper, we proposed a reliable model with the name of 3 Hop-Reliability Model (3H-RM), in which every sender node of each group of three layers will maintain the copy of same successful transferred data packets without creating extra burden on the networks. Simulation results shows that 3H-RM can achieve better delivery ratios as compare to 2H-ACK reliability model without using any additional resources and configurations. Â© 2014 IEEE.